POLITICS OF HEALTHCARE REFORM IN AFRICA: INSIGHTS FROM RURAL NIGERIA: POLITICS OF HEALTHCARE REFORM IN AFRICA - Lawal, Afeez Folorunsho (Faculty of Social and Political Sciences University of Bangka Belitung, 2024)
Healthcare reform is largely a political process which requires a careful analysis for better understanding. The process is often characterized by politics of domination and influence by various actors on the policy scene. This study examines the power relations that shaped the design and implementation of a Community-Based Health Insurance programme in Nigeria. Health policy triangle developed by Walt and Gilson serves as the analytical tool. Using a qualitative method of data collection, this study sheds light on the recent trends in health policy transfer to Africa from the global North and reveals the underlying politics in the design and implementation of a CBHI programme in rural Kwara. Specifically, we highlight the process through which the policy was proposed and accepted. Also, our study shows the political underpinnings of the design and implementation of the policy. Finally, we argue for a need to repurpose the role of the state (i.e. government) towards achieving meaningful development and to gainfully improve social services provisioning, especially in the healthcare sector. Given the importance of healthcare to the well-being of the people, productivity and national development, this study contributes to understanding the issues ‘behind the scenes’ in relation to policy design and implementation.